A New Quadratic CUK-Based Step-Up DC/DC Converter Without Right Hand Plane Zero - Hossein Gholizadeh; Sara Hasanpour (International Journal of Industrial Electronics, Control and Optimization)
In this paper, a new transformerless high step-up DC/DC converter with low input current ripple for renewable energy generation systems. This introduced circuit is based on a conventional quadratic boost converter with a CUK circuit. Therefore, the advantages of Cuk and quadratic boost converters such as continuity of the input and output currents have been maintained. In this suggested topology, switched capacitor and switched inductor techniques are also considered to obtain high voltage gains. The series connection of an inductor with the load causes the converter to have no right half plane zeros (RHPZ) in the transfer function; Thus, the proposed structure is able to provide fast dynamic behavior under the load variation than the other typical counterparts. The other advanced features of the introduced topology are its ultra-high voltage gain, continuous input current with low ripple, low voltage stress, and common ground between the input source and output load. The voltage conversion ratio of the suggested topology for both ideal and non-ideal modes has been provided. The operating principle, steady-state analysis along with comparison study of the proposed converter are discussed in detail. Finally, to confirm the theoretical analysis, a 80 W (20 V/ 160 V) hardware prototype is established.